KEMAMPUAN MEMAHAMI STRUKTUR DAN ISI TEKS CERPEN SISWA KELAS XI SMAN 1 TELUK KUANTAN - Fitriyana, Widya Bitari; Razak, Abdul; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study entitled The Ability to Understand Structure and Content of Short Story Text of XI Grade Students at Senior High School 1 Teluk Kuantan. This study aimed to describe the ability to understand the structure of the short story text at XI grade student of SMAN 1 Teluk Kuantan, describes the ability to understand the content of short story text XI grade student of SMAN 1 Teluk Kuantan, and describe is there a significant relationship between the ability to understand the structure and content of the short story text XI grade student of SMAN 1 Teluk Kuantan. The method used is descriptive method with quantitative approach. Data of this study is the result of taking the test (answers) to understand the structure and content of the text that the author given to the sample, such as 144 students of XI grade at SMAN 1 Teluk Kuantan. The research results obtained are: (1) ability to determine the structure of the short story text XI grade students at SMAN 1 Teluk Kuantan classified as moderate with a value of 81.65%, (2) ability to determine the structure of the text of the short story class XI student of SMAN 1 Teluk Kuantan MIPA classified as moderate with values 78.87%, (3) ability to determine the structure of the text of the short story class XI IPS SMAN 1 Teluk Kuantan is high with a value of 84.65%, (4) ability to determine the structure of the text of the short story class XI student of SMAN 1 Teluk Kuantan women classified as moderate with values 80.80%, (5) the ability to determine the structure of the text of the short story class XI student of SMAN 1 male Teluk Kuantan classified as moderate with a value of 83.03%, (6) the ability to determine the intrinsic elements of text short story class XI student of SMAN 1 Teluk Kuantan is high with a value of 88.74%, (7) ability to determine the intrinsic elements of text short story class XI student of SMAN 1 Teluk Kuantan MIPA is high with a value of 89.44%, (8) ability to determine the intrinsic elements of text short story class XI IPS SMAN 1 Teluk Kuantan is high with a value of 87.77%, (9) the ability to determine the intrinsic elements of short story text XI grade students of SMAN 1 Teluk Kuantan women is high with a value of 89.58%, (10) the ability to determine the intrinsic elements of text short story class XI student of men SMAN 1 Teluk Kuantan is high with a value of 87.39%, (11) the ability to understand the intrinsic elements of short story text XI grade students at SMAN 1 Teluk Kuantan superior to the student's ability to understand the structure of short storiy text.Keywords: the ability to understand the structure, the ability to understand the content, text stories, a class XI student.